Georgia's post-accession structural reform challenges - G. Arveladze; Maarten Smeets (World Trade Organization (WTO), 2017)
The process leading to WTO accession is complex, requires solid domestic coordination mechanisms in the acceding country, a rethinking of its economic and trade policies and significant domestic structural reforms. It often implies the creation of new institutions designed to coordinate and implement the policies at the national level, as was the case in Georgia. The analysis offered in this working paper addresses some of the challenges that Georgia faced during its WTO accession and the many economic reforms that were undertaken after it became a full member of the WTO in 2000. Today, Georgia has one of the most liberal trade regimes and largely benefits from the new trade opportunities that WTO accession has offered. Even though Georgia has been a WTO member for long, it continues its domestic economic reforms in order to further strengthen its international competitiveness for goods and services. This working paper discusses the various measures taken by Georgia and how it uses and implements some of the main WTO provisions to that effect. This includes the ratification of the TFA by Georgia as part of its commitment to reduce transaction costs, enhance efficiency and reduce lengthy and costly administrative processes at the border. Trade capacity building at the technical level has also contributed to human and institutional capacity building in Georgia and developing a better understanding of the rights and obligations of WTO membership thus facilitating Georgia's fuller integration into the multilateral trading system.
Keywords: F13; F15; F53; 330; trade policy; negotiations; structural adjustment; post-accession; policy coherence